المناهج التعليمية ودورها في تعزيز المسؤولية الاجتماعية - كيتا, جاكاريجا (جامعة الوادي University of Eloued, 2016)
هدف هذا البحث إلى التّعرّف على دور المناهج التّعليميّة في تعزيز مسؤولية طلبة التّعليم العالي الشّخصيّة والأسريّة، وتجاه زملائهم وأصدقائهم، وجامعاتهم، واستخدم الباحث المنهج الوصفيّ التّحليليّ، معتمدًا على الدّراسات الّتي تمحورت حول الأدوار المختلفة للمناهج التّعليميّة وأهمّيتها في تعديل السّلوك بصفة عامّة، وتعزيز المسؤولية الاجتماعيّة بصفة خاصّة، وأظهرت النّتائج أنّ للمناهج التّعليميّة بمفهومها الحديث دورًا بارزًا في تعزيز المسؤوليّة الاجتماعيّة لدى الطّلبة، من حيث الاهتمام بتعزيز مفهوم المسؤوليّة الاجتماعيّة بصفة عامّة، ومسؤولية طلبة التّعليم العالي الشّخصيّة والأسريّة، وتجاه زملائهم وأصدقائهم، وجامعاتهم بصفة خاصّة، والتّركيز على الفضائل الإسلاميّة كالإيثار، والنّصح والتّعاون، وغيرها، وذلك من خلال أنشطة تعليميّة متنوّعة. The objective of this research is to determine the role of curriculum in promoting personal and family responsibility of higher education students towards their colleagues and friends, as well as their universities. The researcher used descriptive and analytical approach, relying on studies that focused on different roles of curriculum and its importance in modifying behavior in general, and promoting social responsibility in particular. The results showed that curriculum in its modern connotation, plays a vital role in promoting social responsibility among students. This could be achieved in terms of interest in promoting the concept of social responsibility in general and personal and family responsibility of higher education students, and in relation to their colleagues and friends as well as their universities in particular, and focusing on Islamic virtues such as altruism, advice, cooperation and so on, through a variety of educational activities
لدى طلبة التعليم العالي
مقال
Keywords: التّعزيز- المناهج التّعليمية-المسؤولية الاجتماعيّة-التّعليم العالي; Promotion, curriculum, social responsibility, higher education.